Children as People of The Crime of Theft with Violence and Incurment - Teguh Apriyanto; Hidayati Hidayati (Rechtsnormen: Journal of Law, 2024)
Background: Juvenile delinquency, including crimes committed by children, is a pressing social issue in various regions. Children are often unable to fully comprehend and take responsibility for their actions due to their developmental stage and environmental influences. To address this, the judicial process for children differs from that of adults, aiming to minimize psychological harm. Law Number 11 of 2012 on the Juvenile Criminal Justice System serves as the legal framework to protect children’s rights while addressing their offenses. Objectives: This study aims to analyze the occurrence of violent theft by children, understand contributing factors, and evaluate the application of the juvenile justice system in handling such cases.. Methods: The study uses a qualitative approach, analyzing legal documents, court cases, and interviews with stakeholders, including law enforcement, psychologists, and social workers, to understand the legal and social dimensions of violent theft involving children. Research Findings: The findings reveal that environmental factors, lack of supervision, and socio-economic issues are significant contributors to children’s involvement in violent theft. The juvenile justice system plays a crucial role in rehabilitating offenders and preventing recidivism. Conclusion: Addressing juvenile delinquency requires an integrated approach involving legal, social, and psychological interventions. Strengthening family and community support systems is vital to reducing the incidence of violent theft by children.